La ricerca del nucleo psicopatologico della schizofrenia: i disturbi del Sé. Introduzione - Brandizzi, Martina; Dell’Erba, Alice; Lo Cascio, Nella; Masillo, Alice; Monducci, Elena (Il sogno della farfalla, 2016)
This text introduces a monographic issue, based on the recent work carried out by a research group on early detection of schizophrenia. Its objective is to illustrate the main features, the limits, the critical points of an interesting research, which was developed in Denmark and coordinated by Josef Parnas. This research suggests that classic psychopathology concepts should be recovered in order to detect the core features of schizophrenia, which these investigators identified in self-disorders. The first article, which describes the main historical phases of research on the Self, is followed by interviews with two experts, who are Parnas himself and Andrea Raballo. Then, the Italian translation of a recent article on the relevance of self-disorders within the context of early intervention in schizophrenia is proposed. The translation of the article is followed by an overview of international studies on the presence of self-disorders in subjects at high risk of developing psychosis. The issue ends with a study on schizotypal personality disorders and an article that, given the limits and the critical points of research on self-disorders, suggests a different evaluation of these symptoms in the light of Human Birth Theory.